Numerical investigation of laminar flow and thermal characteristics of tangential cooling air jet in a sudden expansion channel - Pishgahi, Asghar (2012)
This thesis describes a study of tangential jet flow in a sudden expansion channel referred to as a Backward Facing Step (BFS). A two dimensional laminar air flow was investigated numerically by introducing a cooling air flow injected tangentially through a slot on the step. The goal of the study is to gain an insight on the relationships between the axial momentum of the cooling air and characteristics of the flow and heat transfer by performing systematic assessment on the geometrical, kinematic and dynamic properties of the fluid. The Top-wall had a constant temperature (Tw) of 35◦C. All other walls were adiabatic. The static temperatures of the mainstream T∞ and tangential jet flows (Tc) were assumed constant at 50◦C and 20◦C respectively. The BFS had an expansion ratio (ER) of 2. In the numerical experiments, the main channel Reynolds number (Re) was varied from 100 to 800 for a range of velocity ratios (Λ=Vj/V∞) between 0 (backward facing step flow) and 1.0 (tangential jet flow in BFS), and of ratios of slot to step heights (ℓ=slot height/step height) between 0.1 and 0.5. The simulations were performed for air with a constant Prandtl number (Pr) of 0.71. The governing equations of motion and energy for two-dimensional laminar flow were discretized by a finite volume method. The resultant algebraic equations incorporated in the modified TEACH-T code were solved by treating the combined convective and diffusion terms using the hybrid differencing scheme. The elliptic solver was modified to reduce the computational time by integrating the prediction from multiple solution sub-domains. The BFS flow is characterized by the primary and secondary recirculating flows on the Top-wall and Low-wall respectively, and the occurrence of small recirculating flow at the corner regions. The tangential jet flow is introduced into the main channel. The thermal analysis was presented to investigate the influence of convection heat transfer through the Top-wall. Two simulated conditions were studied; BFS flow with and without tangential jet flow. The predictions were compared against previous studies. For constant values of Re, the strength of primary and secondary recirculation were reduced with increasing ℓ. Increasing the axial momentum of the jet produced larger friction coefficient but reduced rapidly the air temperature in the corner region. The occurrence of film flow in the main channel by the tangential jet flow eventually reduces the amount of convective heat transfer. At constant ℓ, the Moffat eddy and the secondary recirculation flow were removed, and the strength of the primary recirculating flow was attenuated for Λ>0. The tangential jet flow affects the rate of heat transfer and reduces the maximum Nu. Increasing Λ significantly affects the film cooling effectiveness (η) particularly in the corner region compared to ℓ and Re. The uncertainty analysis and statistical analysis of the numerical results shows that the predictions were in acceptable and reliable range.